A fatal case of pure metaphyseal chondroblastoma. (23rd August 2013) - Binesh, Fariba; Moghadam, Reza Nafisi; Abrisham, Jalil
Abstract : The chondroblastoma (CB) is a rare cartilaginous tumour; it represents less than 1% of all bone tumours. It is mostly localised at the level of the epiphysis of long bones. We report a fatal case of pure metaphyseal CB of the tibia in a 9-year-old boy whose pulmonary metastases developed soon after operative therapy of the primary tumour.